French Сolonizers on “Other” Сolonizers: Britain and Germany in Narratives of Paul Leroy‑Beaulieu and Jules Ferry - Taisiia M. Demicheva (Журнал Фронтирных Исследований)
The article examines the reflection of the images of France’s primary adversaries in colonial politics, Britain and Germany, in the narratives of the principal advocates of French colonization, namely Jules Ferry, who held numerous positions in the Third Republic’s government, and Professor Paul Leroy-Beaulieu from College de France.